GATA4 Variants in Individuals With a 46,XY Disorder of Sex Development (DSD) May or May Not Be Associated With Cardiac Defects Depending on Second Hits in Other DSD Genes - Martinez de LaPiscina, Idoia; de Mingo, Carmen; Riedl, Stefan; Rodriguez, Amaia; Pandey, Amit V.; Fernández-Cancio, Mónica; Camats, Nuria; Sinclair, Andrew; Castaño, Luis; Audi, Laura; Flück, Christa E. (Frontiers in Endocrinology, 2018)
Disorders of sex development (DSD) consist of a wide range of conditions involving numerous genes. Nevertheless, about half of 46,XY individuals remain genetically unsolved. GATA4 gene variants, mainly related to congenital heart defects (CHD), have also been recently associated with 46, XY DSD. In this study, we characterized three individuals presenting with 46,XY DSD with or without CHD and GATA4 variants in order to understand the phenotypical variability. We studied one patient presenting CHD and 46,XY gonadal dysgenesis, and two patients with a history of genetically unsolved 46,XY DSD, also known as male primary hypogonadism. Mutation analysis was carried out by candidate gene approach or targeted gene panel sequencing. Functional activity of GATA4 variants was tested in vitro on the CYP17 promoter involved in sex development using JEG3 cells. We found two novel and one previously described GATA4 variants located in the N- terminal zinc finger domain of the protein. Cys238Arg variant lost transcriptional activity on the CYP17 promoter reporter, while Trp228Cys and Pro226Leu behaved similar to wild-type. These results were in line with bioinformatics simulation studies. Additional DSD variations, in the LRP4 and LHCGR genes respectively, were identified in the two 46,XY individuals without CHD. Overall, our study shows that human GATA4 mutations identified in patients with 46,XY DSD may or may not be associated with CHD. Possible explanations for phenotypical variability may comprise incomplete penetrance, variable sensitivity of partner genes, and oligogenic mechanisms.